Links between recognition and degradation of cytoplasmic viral RNA in innate immune response. (8th December 2015) - Oshiumi, Hiroyuki; Mifsud, Edin J.; Daito, Takuji
Summary: Recognition and degradation of viral RNA are essential for antiviral innate immune responses. Cytoplasmic viral RNA is recognized by retinoic acid‐inducible gene I (RIG‐I)‐like receptors, which trigger type I interferon (IFN) production. Secreted type I IFN activates ubiquitously expressed type I IFN receptor and induces IFN‐stimulated genes (ISGs). To suppress viral replication, several nucleases degrade viral RNA. RNase L is an ISG with endonuclease activity that degrades viral RNA, producing small RNA that activates RIG‐I, resulting in the amplification of type I IFN production. Moreover, recent studies have elucidated novel links between viral RNA recognition and degradation. The RNA exosome is a protein complex that includes nucleases and is essential for host and viral RNA decay. Although the small RNAs produced by the RNA exosome do not activate RIG‐I, several accessory factors of the RNA exosome promote RIG‐I activation. Zinc‐finger antiviral protein (ZAP) is an accessory factor that recognizes viral RNA and promotes viral RNA degradation via the RNA exosome. ZAPS is an alternative splicing form of ZAP and promotes RIG‐I oligomerization and ATPase activity, resulting in RIG‐I activation. DDX60 is another cofactor involved in the viral RNA degradation via the RNA exosome. The DDX60 protein promotes RIG‐I signaling in a cell‐type specific manner. These observations imply that viral RNA degradation and recognition are linked to each other. In this review, I discuss the links between recognition and degradation of viral RNA. Copyright © 2015 John Wiley & Sons, Ltd.